Surgical Management of Comminuted, Displaced Greater Tuberosity Fractures: A New Technique of Subacromial Spacer on Top of Double-Row Suture Anchor Fixation - Naggar, Leslie (Joints, 2018)
Arthroscopic treatment of greater tuberosity (GT) fractures has been previously described. Arthroscopy allows identifying and addressing coexisting injuries, such as rotator cuff tears, labrum, or superior labrum anterior and posterior lesions, which are often present. Fracture comminution precludes the use of rigid fracture fixation with screws and arthroscopic rotator cuff repair is performed instead. Recent articles have depicted the role of the balloon-shaped subacromial spacer in massive and irreparable rotator cuff tears. The purpose of this technical report is to outline another use of the spacer in patients with a GT fracture. The concept is to leverage the advantage of the compression effect of the subacromial spacer to prevent displacement of the GT fracture and allow early active shoulder rehabilitation, especially in comminuted or eggshell fractures when rigid fixation is not feasible.
Keywords: greater tuberosity; fracture; arthroscopy; subacromial spacer; balloon